Reforma agrária: condições socioeconômicas do assentamento Poço dos Negros no município de Altos - Piauí - Ramos, Patrícia de Brito (2008)
This thesis aims to understand and analyze the socioeconomic conditions of the Settlement Well of Black, located in the municipality of Altos, in the state of Piauí, at 37 km from its capital Teresina. The settlement has 35 families and a population of 160 people, registered and settled by the National Institute of Colonization and Agrarian Reform - INCRA a total area of 1.044,7164 ha (hum one thousand forty-four hectares, seventy one ares and sixty four centiares ), which took possession on 08/02/2006. This community has been chosen as the object of our study, motivated by the proximity to our capital, Teresina, by integrating the programme of land reform of Piauí and the particular interest in obtaining grants consistent on the reality of the settlers and their families, aiming to make an with a more effective job of social responsibility developed since 2005 by the Center for Research, Extension and Post- Graduate School of San Gabriel, in which we work. This study seeks to address the Agrarian Reform, its historical background and methods of settlement in Brazil, highlighting the socio-economic conditions and environmental settlement in the study. The methods used in the research of the field were explorativo-qualitative and quantitative-deductive, achieved through literature, interviews, consultations with technical, associations, visits spot, among others. The study shows improvement, though modest, in the social and economic conditions of families settled, they have on agriculture their main source of production and income. The basic infrastructure of health, housing and education there is, however needs to be improved and implemented other essential services such as: energy, roads, communication, transportation among others. The settlers subject of this study demonstrate be aware that many shares in the agricultural sector have been made, but also are aware that others are needed as subjects and that incorporating the process of deployment of the Black Assentamento Well collectively share with the public power the success or weaknesses of the shares in this implemented.